The rate of DNA synthesis in ovaries, fat body cells, and pericardial cells of the bumblebee (Bombus terrestris) depends on the stage of ovarian maturation - Zavodska, Radka; Sehadova, Hana (Frontiers in Physiology, 2023)
Bumblebees are important pollinators of plants worldwide. By studying the process of oogenesis, we can understand their ontogenetic developmental strategy, leading to successful artificial rearing. We describe the anatomy of the ovary of the bumblebee Bombus terrestris using 3D reconstruction by confocal microscopy. We found that during oogenesis, an oocyte is accompanied by 63 endopolyploidy nurse cells that are gradually absorbed by the oocyte during vitellogenesis. We monitored the rate of DNA synthesis in vivo over the course of 12 hours in ovaries, fat body, and pericardial cells in B. terrestris queens and workers of different ages. The DNA replication activity was detected on the basis of visualization of incorporated 5-ethynyl-2´-deoxyuridine. DNA synthesis detected in differentiated nurse cells indicated endoreplication of nuclei. The dynamics of mitotic activity varied among different ages and statuses of queens. In 3- to 8-day-old virgin queens, intense mitotic activity was observed in all tissue types investigated. This might be related to the initial phase of ovarian maturation and the development of the hepato-nephrotic system. In 15- to 20-day-old mated pre-diapause queens, DNA synthesis was exclusively observed in the ovaries, particularly in the germarium and the anterior part of the vitellarium. In 1-year-old queens, replication occurred only in the peritoneal sheath of ovaries and in several cells of the fat body. The similar DNA synthesis patterns in the ovaries of mated pre-diapause queens, ovipositing workers, and non-egg–laying workers show that mitotic activity is related not only to age but also to the stage of ovarian maturation and is relatively independent of caste affiliation.